Opinions of Saudi elites towards the credibility of electronic press sites and their relationship to degree of dependency - Almarzouqi, Norah Saleh (Journal of Humanities & Social Sciences, 2020)
The study aimed to identify the credibility level of electronic press sites and their correlation with the reliability level as seen by the Saudi elite. To verify the aim, the study followed the descriptive approach. The study sample consisted of (102), representing the audience of the Saudi academic elite and media who use Internet as general and electronic press sites in particular, (Media faculty members of Saudi universities), the study was applied to the Saudi newspaper websites such as (Okaz newspaper, Middle East newspaper, Riyadh newspaper, and Sabk newspaper). The researcher conducted special criteria for the study of website reliability standards of the newspaper. The field study, survey applying, and data collection were conducted in October and November 2018. This study showed the following results: There is a statistically significant correlation between the exposure intensity of the Saudi elite to the study sample websites and their reliability level on it. This means that the greater the exposure of the Saudi elite to the electronic press sites, the greater the level of their reliability on it, and proved a statistically significant correlation between the intensity of the exposure of the Saudi elite to the electronic press sites of the study sample and the credibility level. It also showed a significant correlation between the intensity of the exposure of the Saudi elite to the website’s contents of the study press sample and the motivations of its pursuance in the future. The study concludes a number of recommendations, the most important of which is that the press websites should be concerned with the standard of interaction in terms of communication with the author, and conduct studies on the contact persons who working in the field of newspaper websites to find out the most important pressures and factors affecting their credibility of transferring information.